A review on determinants of depression among adult prisoner - Subbarao, Gunenthira Rao; Abdul Manaf, Rosliza; Minhat, Halimatus Sakdiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Prisoner tend to be marginalized and deprived that it burdens them with psychological trauma, predominantly depression. This review will identify the determinants of depression among adult inmates. Literatures published from 2012 to March 2017 were searched from various databases. Inclusion criteria were English full text, adults with a diagnosis of depression while exclusion criteria were diagnostic instruments, clinical or drug trials. The review adhered to Preferred Reporting Items for Systematic Review and Meta-Analyses: The PRISMA Statement reporting. A total of 168 studies were identified although only 14 studies were eligible for final review. Factors associated with inmates’ depression range from the potentially modifiable to non-modifiable. Recognized modifiable factors were psychological, family support, and environment while non-modifiable were biological, demographic, individual, and social. Determinants identified should be addressed in formulation of better targeting therapy, in terms of both prevention and treatment of depression among inmates.